PENGARUH RETURN ON ASSET, DEBT TO ASSET RATIO, DAN KONEKSI POLITIK TERHADAP AGRESIVITAS PAJAK - Tubagus Indra Rahmadi; Siti Sarpingah (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This research aims to know the influence of Return on Asset (ROA), Debt to Asset Ratio (DAR) and political connection on tax aggressiveness (Empirical Study of Various Industries Manufacturing Sector Listed on The Indonesia Stock Exchange on Year 2016 to 2020. In this study was selected using purposive sampling method. The population in this research are various industries manufacturing sector listed on the Indonesia Stock Exchange on year 2016 to 2020 totaling 53 firms. However, there is only 9 firm sample that meet the criteria. The number of samples that used in this study is 45 samples. The analytical method used in this study is multiple regression using SPSS version 20. The results of the study indicate that: Return on Asset (ROA) has a negative effect on tax aggressiveness. While Debt to Asset Ratio (DAR) and political connection have no effect on tax aggressiveness.